Preoperative factors and four-year decompressive laminectomy success in symptomatic lumbar spinal stenosis - Fields, Daryl P.; Holloway, Kathryn Lois; Levin, Emily; Keyserling, Harold; Nortman, Samuel; Krein, Sarah L.; Gentili, Amilcare; Katz, Jeffrey N.; Perera, Subashan; Weiner, Debra K. (Frontiers in Musculoskeletal Disorders, 2025)
Background/Context: Decompressive laminectomy (DL) for lumbar spinal stenosis (LSS) is the most common spinal surgery for older adults. Biopsychosocial factors are associated with one-year outcomes in these patients. While most surgical failures occur within twelve-months, some are delayed and factors responsible for delayed surgical failure are poorly understood. Purpose: We sought to identify preoperative factors associated with long-term surgical success as defined by the Brigham Spinal Stenosis (BSS) questionnaire. Study Design/Setting/Patient Sample: Within this prospective cohort study we used logistic regression modeling to identify pre-operative biopsychosocial factors that predict four-year DL success in 110 prospectively evaluated veterans who underwent DL without fusion for LSS. Outcome Measures/Methods: A questionnaire was used to evaluate BSS Spinal Stenosis outcomes at four-years post DL. Results: Overall, 69 participants (63%) demonstrated four-year surgical success -sustained improvement in at least 2 of the 3 BSS domains (symptoms, function, and satisfaction). Greater catastrophizing (OR for 2 points 0.92 [0.84-1.00]; p=0.0512) and longer symptom duration (OR for twelve-months 0.96 [0.93-0.99]; p=0.0231) were associated with lower likelihood of success, while presence of moderate/severe stenosis (OR 7.16-7.39; p=0.0195-0.0260), college education (OR 2.93 [1.27-6.77]; p=0.0120) and greater treatment credibility (OR for 10 points 1.35 [1.10-1.66]; p=0.0048) with greater likelihood of success in bivariate analyses. Symptom duration (OR 0.96 [0.92-0.99]; p=0.0208), treatment credibility (OR 1.51 [1.15-1.98]; p=0.0031) and stenosis severity (OR 14.4-17.4; p=0.0045-0.0055) constituted a parsimonious set of factors in multivariable modeling. Conclusions: Further work is needed to definitively identify pre-operative factors that predict long-term outcomes. This may facilitate more accurate patient selection and counseling for patients undergoing DL for LSS.